A formação do intérprete de libras para o ensino de ciências lacunas refletidas na atuação do TILS em sala de aula - Rieger, Camila Paula Effgen (2016)
This work has as its main theme the academic education of the Interpreter of Sign Language (ISL) in acting as a mediator of communication among teachers and deaf students in regular public institutions. It presents some considerations about barriers faced by the ISL when dealing with technical and scientific terms related to specific subjects that are not part of their current vocabulary or find no equivalent in sign language and how their academic skills contribute to the erect these obstacles to the process of interpretation. Starting from the author´s experience, graduated in pedagogy, acting as an interpreter of Portuguese/Libras ( acronymous to Brazilian Sign Language) in a subjects for Exact Sciences, this research seeks to broaden perspectives on issues related to the training path of ILS and their work at the educational institutions. Initially it is presented an analysis of articles published in the National Research Congress Proceedings in Translation and Interpretation of Libras and Portuguese with attention to those articles whose theme is the training of ILS. This analysis highlights the lack of discussion of the training activities for acting in science teaching as a way to overcome language barriers found in the act of interpretation. In order to analyze the detachment between the knowledge acquired by the ILS in action during their training (initial or ongoing) and the subjects of the areas of Exact and Natural Sciences, it was proposed a questionnaire answered by the ILS from the cities of Foz do Iguaçu and Cascavel. The analysis of the questionnaire answers it is observed that the academic education of ILS focuses on Humanities courses and that, whether in postgraduate level or other training processes, there is no attention to training for acting in subjects of Exact Sciences.